Composition optimization of Ni-Zn ferrites for magnetic hyperthermia: structural, morphological and spectroscopic study - D. Parajuli; P. V. Ramana; N. Murali; S. Bista; M. Sharma; K. Samatha (Bibechana, 2024)
The optimization of the appropriate composition is necessary for the characteristics suitable for magnetic hyperthermia by varying the amount of iron in the ferrite composition. The NiZn ferrite with the composition Ni0.65Zn0.35Fe2O4, Ni0.65Zn0.40Fe1.95O4, and Ni0.60Zn0.35Fe2.05O4 indicated by IN, IE, and ID respectively were synthesized from sol-gel approach. XRD shows cubic spinel structure except for one extra peak in all three samples (IN 800℃; IE 800℃, and ID 900℃; 800℃, 900℃ and 1000℃) around 2θ= 40.9° is related to the iron oxide (gFe2O3) and is related to JCPDS 89-8104). The formation of the additional peak is due to the diffusion of atoms in the heating process. The variations in crystallite size and particle size due to iron content. Their effect on magnetic properties and hence in hyperthermia are under study.